2005
DOI: 10.1098/rspb.2004.2924
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of brain regions to habitat complexity: a comparative analysis in bats (Chiroptera)

Abstract: Vertebrate brains are organized in modules which process information from sensory inputs selectively. Therefore they are probably under different evolutionary pressures. We investigated the impact of environmental influences on specific brain centres in bats. We showed in a phylogenetically independent contrast analysis that the wing area of a species corrected for body size correlated with estimates of habitat complexity. We subsequently compared wing area, as an indirect measure of habitat complexity, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 37 publications
3
104
1
Order By: Relevance
“…Correlations between independent contrasts of variables were examined using least squares linear regressions with the models constrained to go through the origin. Results from species-level analyses can also be confounded by physiological and ecological 'grade shifts,' as previous studies have demonstrated significant effects of echolocational ability and diet (fruit versus non-fruit) on relative brain mass in bats (Barton et al 1995;Jones & MacLarnon 2004;Safi & Dechmann 2005). We thus took a conservative approach, investigating each correlation both within all species and discretely for each of the above grades.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between independent contrasts of variables were examined using least squares linear regressions with the models constrained to go through the origin. Results from species-level analyses can also be confounded by physiological and ecological 'grade shifts,' as previous studies have demonstrated significant effects of echolocational ability and diet (fruit versus non-fruit) on relative brain mass in bats (Barton et al 1995;Jones & MacLarnon 2004;Safi & Dechmann 2005). We thus took a conservative approach, investigating each correlation both within all species and discretely for each of the above grades.…”
Section: Methodsmentioning
confidence: 99%
“…Various adaptive explanations for the remaining variation include the need for enhanced or specialized sensory systems (Barton et al 1995), diet (Jones & MacLarnon 2004) and spatial ecology (Safi & Dechmann 2005). In addition, the 'social brain' (or 'Machiavellian intelligence') hypothesis, which contends that increasing social complexity enhances cognitive arms races in which relatively large-brained individuals are better able to manipulate the behaviour of others to favour the manipulator's own needs (Byrne & Whiten 1997), has been supported by positive relationships between brain size and social group size (Dunbar 1995) or deception rate (Byrne & Corp 2004) among primates.…”
Section: Introductionmentioning
confidence: 99%
“…Our sample includes two basal insectivorous species (Macrotus waterhousii and Mimon crenulatum), two nectar-feeding bats (Glossophaga soricina and Anoura geoffroyi) and two frugivores (Carollia perspicillata and Artibeus jamaicensis; figure 1). Comparative neurobiological studies have consistently demonstrated that fruit-and nectar-feeders have larger olfactory brain structures compared with insectivores of the same brain and body size [11][12][13]. This has led some authors to suggest that diet is a major driving force in the evolution of differently sized olfactory regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yet a wealth of studies have shown that the hippocampus plays an essential role in a variety of forms of spatial learning and memory in laboratory mice and rats, monkeys, and humans, as well as several other undomesticated species including fish, reptiles, bats, and a variety of avian and rodent species (e.g., Hampton & Shettleworth, 1996;Vargas, Petruso, & Bingman, 2004). Also, several studies have compared hippocampal anatomy within closely related species of rodents, birds, and bats, as well as humans with different occupations, providing fascinating evidence that hippocampal size is related to greater use of space in natural habitats (e.g., Pleskcheva et al, 2000;Safi & Dechmann, 2005;Jacobs, Gaulin, Sherry, & Hoffman, 1990;Jacobs & Spencer, 1994;Lucas, Brodin, de Kort, & Clayton, 2004;Maguire, Woollett, & Spiers, 2006).…”
Section: Spatial Functions Of the Hippocampusmentioning
confidence: 99%